BACTERIAL FLORA ASSOCIATED WITH DISEASED FISH AND THEIR ANTIBIOGRAM - Abraham, T. Jawahar; Sasmal, Debasis; Banerjee, Tirthankar (Journal of Indian Fisheries Association, 2015)
Bacterial flora associated with tail rot I fin rot of Carassius auratus, Xiphophorus helleri and hemorrhagic ulcers of Clarias spp were studied. Sensitivity pattern of 33 isolates comprising Aeromonas spp, Pseudomonas spp and Gram-positive rods from diseased C. auratus, X. helleri and Clarias spp were screened against six broad-spectrum antibiotics viz. ciprofloxacin, chloramphenicol, co-trimoxazole, gentamycin, nitro-furantoin and oxytetracycline. Ciprofloxacin was the most effective in inhibiting bacteria at 0.05 - 0.10 p.g/ml level. About 44% of Pseudomonas spp. were resistant to nitrofurantoin. Resistance to oxytetracycline was seen in 27% of Aeromonas spp Gram-positive rods were comparatively more resistant to antibiotics. The multiple antibiotic resistance was seen in 21% of the bacterial isolates of diseased fish. Key words: Fish pathogens, Antibiogram